Older Australians' perceptions of alcohol‐related harms and low‐risk alcohol guidelines. (12th December 2019) - Chapman, Janine; Harrison, Nathan; Kostadinov, Victoria; Skinner, Natalie; Roche, Ann
Abstract: Introduction and Aims: Australia has an ageing population. Given the concomitant increase in the numbers and proportion of risky drinkers among older adults, research examining contributory factors is a priority. The current study examined older adults' estimates of the NHMRC low‐risk drinking guidelines, consumption patterns and associated harms and self‐identification of drinking type. Design and Methods: Data from respondents aged 50+ years ( N = 11 886) in the 2016 National Drug Strategy Household Survey were subjected to secondary analyses. Estimates of low‐risk drinking levels, perceived level of harm from current drinking, self‐identification of drinking type and awareness of standard drinks and labelling were included. Data were examined for those aged 50–59 years and 60+. Results: Seventeen percent of older Australians drank at both long‐term and short‐term risk levels. Approximately 39% of males and 11% of females overestimated the long‐term low‐risk levels and 54% of males and 20% of females overestimated the short‐term low‐risk levels. Overestimation was highest among risky drinkers. Most older risky drinkers were aware of standard drinks and labelling; however, less than half perceived their drinking as harmful, instead identifying as social drinkers. Discussion and Conclusions: Although substantial gaps are evident in older respondents' estimates of low‐risk drinking, additional public awareness campaigns are likely to be of limited use. Older peoples' engagement with the public health system presents 'windows of opportunity' to provide targeted, age‐appropriate harm reduction strategies. Appropriate intervention and policy responses are required to direct resources to this emerging area of concern.